Answer:
x = 2.3 and x = 3.7
Explanation:
For an equation "ax2 + bx + c = 0", the values of x which are the solutions of the equation are given by the quadratic formula as
x = -b ± √(b² − 4ac) / 2a
Given in the question that
5x² - 3x = 7
5x² - 3x - 7 = 0
a = 5
b = -3
c = -7
Put these value in quadratic equation
x = -b ± √(b² − 4ac) / 2a
x = -(-3)± √((-3)² - 4(5)(-7) ) / 2(5)
x = 3 ± √(9 - 4(5)(-7) ) / 10
x = 3 ± √(9 + 140 ) / 10
x = 3 ± √(9 + 140 ) / 10
x = 3 ± √(149 ) / 10
x = 3 ± 7 / 10
x = 3 - ( 7 / 10 ) and x = 3 + 7 / 10
x = 23/10 and x = 37/10
x = 2.3 and x = 3.7